The Digestive Master of the Insect World: The Digestive System and Application Value of Mealworms - Liu Jiacheng (BIO Web of Conferences, 2025)
Mealworms (Tenebrio molitor L.) are recognized in the insect realm as “digestive masters” due to their remarkable digestive capabilities. Their digestive system exhibits a high degree of adaptability, enabling the effective breakdown of various complex substances. This study reviews the adaptability of the mealworm digestive system, with a particular emphasis on its performance across diverse food sources and environmental conditions. Additionally, it examines potential microbial mechanisms identified in the literature, highlighting the unique advantages of mealworms in degrading complex organic materials. By synthesizing these findings, the study outlines the substantial application potential of mealworms in waste resource utilization and biodegradation. This research establishes a theoretical foundation and reference framework for further exploration of mealworms in waste treatment and biodegradation.